Reaching Viral Suppression Among People With HIV With Suspected Treatment Failure who Received Enhanced Adherence Counseling in Southern Nigeria: A Retrospective Analysis. (15th December 2022) - Akpan, Uduak; Nwanja, Esther; Ukpong, Kufre-Abasi; Toyo, Otoyo; Nwaokoro, Pius; Sanwo, Olusola; Gana, Bala; Badru, Titilope; Idemudia, Augustine; Pandey, Satish Raj; Khamofu, Hadiza; Bateganya, Moses
Abstract: Background: This study assessed viral load (VL) testing and viral suppression following enhanced adherence counseling (EAC) among people with HIV (PWH) with suspected treatment failure and identified factors associated with persistent viremia. Methods: We conducted a retrospective review of electronic medical records of PWH aged 15 years or older who had received antiretroviral therapy (ART) for at least 6 months as of December 2020 and had a high viral load (HVL; ≥1000 copies/mL) across 22 comprehensive HIV treatment facilities in Akwa Ibom State, Nigeria. Patients with HVL were expected to receive 3 EAC sessions delivered in person or virtually and repeat VL testing upon completion of EAC and after documented good adherence. At 6 months post–EAC enrollment, we reviewed the data to determine client uptake of 1 or more EAC sessions, completion of 3 EAC sessions, a repeat viral load (VL) test conducted post-EAC, and persistent viremia with a VL of ≥1000 copies/mL. Selected sociodemographic and clinical variables were analyzed to identify factors associated with persistent viremia using SPSS, version 26. Results: Of the 3257 unsuppressed PWH, EAC uptake was 94.8% (n = 3088), EAC completion was 81.5% (2517/3088), post-EAC VL testing uptake was 75.9% (2344/3088), and viral resuppression was 73.8% (2280/3088). In multivariable analysis, those on ART for <12 months ( P ≤ .001) and those who completed EAC within 3 months ( P = .045) were less likely to have persistent viremia. Conclusions: An HVL resuppression rate of 74% was achieved, but EAC completion was low. Identification of the challenges faced by PWH with a higher risk of persistent viremia is recommended to optimize the potential benefit of EAC. Abstract : In a retrospective cohort of 3, 088 persons with high HIV viral load (>1000copies/mL) successfully enrolled for a 3-month enhanced adherence counseling across multiple HIV treatment facilities in southern Nigeria, a repeat viral load showed up to 74% viral suppression.